Self Assessment System, Tax Avoidance, Tax Rate, Tax Evasion on the Effectiveness of Corporate Income Tax Revenue during the COVID-19 Pandemic - I Gede Ary Wirajaya; Anggi Anggita Putri (Universitas Pendidikan Ganesha, 2023)
The effectiveness of corporate income tax revenue is the ability and ability of the government to collect taxes obtained from corporate income tax according to the applicable rates and based on the amount of tax revenue that has been targeted. This study aims to determine the effect of Self assessment system, Tax Avoidance, Tax Rates and Tax Evasion on the Effectiveness of Corporate Income Tax Revenue during the Covid-19 pandemic. Data collected by distributing questionnaires to respondents via google form. The population used in this study were all Account Representatives of KPP West Denpasar and KPP East Denpasar. The sample used in this study were 48 Account Representatives using data collection techniques with non-probability sampling method. Analysis of the data used is by using the method of multiple linear analysis. The results of this study indicate that the Self Assessment System, Tax Rates, Tax Avoidance and Tax Evasion have an effect on the Effectiveness of Corporate Income Tax Revenue.